Myosin 1g as a high-risk biomarker in a pediatric patient with lineage switch from acute lymphoblastic leukemia to myeloid phenotype - Janeth E. Araujo-Cárdenas; Miguel A. Rodríguez-Ruiz; Jaime A. López-Valdez; Rosa I. Rodríguez-Téllez; Yanelly Garfias-Gómez; Israel Parra-Ortega; Genaro Patiño-López (Permanyer, 2023)
Background: Myosin 1g (Myo1g) has recently been identified as a potential diagnostic biomarker in childhood acute lymphocytic leukemia (ALL). Case report: We describe the case of a 1-year-old Mexican female patient. Although initially studied for hepatomegaly, an infectious or genetic etiology was excluded. Liver biopsy showed infiltration by neoplastic B-cell precursors (BCPs), and bone marrow (BM) aspirate showed 14.5% of BCPs. In a joint session of the oncology, hematology, and pathology departments, low-risk (LR) BCP-ALL of hepatic origin with aberrant myeloid markers was diagnosed. Although treatment was initiated, the patient presented early with BM relapse. Modest overexpression of Myo1g was observed from the onset. However, at the end of the steroid window, expression increased significantly and remained elevated during this first relapse to BM. The parents refused hematopoietic stem cell transplantation, but she continued chemotherapy. After a second BM relapse at 5 years of age, the phenotype switched to myeloid. Her parents then opted for palliative care, and the patient died two months later at home. Conclusions: This case shows the potential use of Myo1g in clinical practice as a high-risk indicator. Myo1g monitoring may reveal a high risk and relapse trend, even when typical parameter values are not altered: Myo1g could be used to classify patients from low to high risk from diagnosis, allowing patients to promptly receive the best treatment and potentially modifying prognosis and survival.